Hey, little ant - Hoose, Philip M., 1947-; Hoose, Hannah; Tilley, Debbie (Berkeley, Calif. : Tricycle Press, 1998)
A song in which an ant pleads with the kid who is tempted to squish it. (Gr. PreK-2)
NP
Keywords: Children's songs -- Texts; Ants -- Songs and music; Songs